Pemanfaatan Tepung Kelakai Sebagai Bahan Pangan Alternatif Sumber Zat Besi Dalam Subtitusi Produk Cookies Chickpea Untuk Ibu Hamil Anemia - Angestya Verani Fahriza; Ibnu Malkan Bakhrul Ilmi; Sintha Fransiske Simanungkalit (Jurnal Pangan dan Gizi, 2021)
The prevalence of anemia in pregnant women in Indonesia increased significantly from 37.1% in 2013 to 48.9% in 2018. Anemia can be prevented and treated by consuming iron source foods. The purpose of this research is to utilize kelakai flour as an alternative food source of iron in the substitution of chickpea cookies products for pregnant women with anemia. The study used a Complete Randomized Design (RAL) consisting of three levels of treatment and two repetitions, namely: Comparison of chickpea flour and kelakai flour F1 (30g : 15g), F2 (27.5g: 17.5), F3 (25g : 20g). Analysis of organoleptic test data and chemical properties analysis used Kruskall Wallis test and ANOVA test. The results showed that in organoleptic testing substitution of kelakai flour had a real effect (p<0.05) on taste and aroma parameters. The result of substitution kelakai flour had a real effect (p<0.05) on ash, protein and iron content of cookies. Cookies F3 is the best formulation that had a chemical composition; 463.02 kcal of energy, 17.18% fat, 10.23% protein, 66.87% carbohydrates, 6.97mg of iron. The iron content of cookies F3 has qualified the claim of iron source of food products required by BPOM.